Water Conflict Between Fishermen And The Shrimp Farm Industry (Case Study Of Nglebeng Village, Panggul District, Trenggalek Regency) - Dinasty Pujayani, Sindhu; Tri Kartono, Drajat; Utami, Trisni (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This research aims to determine the conflict between fishermen and shrimp farming entrepreneurs in Nglebeng Village, Trenggalek Regency and the conflict resolution used. This qualitative research uses a case study approach carried out in Nglebeng Village. Using purposive sampling, the author collected data through observation and in-depth interviews with informants with specific criteria. In terms of validity testing, the author uses the triangulation technique, which is done by collecting similar data and comparing the data to obtain a picture of the information. Data analysis was carried out using interactive analysis techniques. The research results concluded that differences in interests between groups of fishermen and shrimp farming entrepreneurs caused the conflict between fishermen in the waters of Konang Nglebeng Beach. In this case, it is related to environmental pollution. Conflicts are caused by differences in interests held by each group, where shrimp farmers want to develop their business and fishermen want the sea not to be polluted by waste because it can disrupt the ecosystem of marine creatures. Conflict resolution in dealing with the problem of shrimp farms and fishermen is solved using Dahrendorf theory, namely Conciliation, Mediation, and Arbitration.